Avaliação dos parâmetros de deposição e dos tratamentos superficiais dos substratos nas propriedades ópticas e na morfologia de filmes absorvedores à base de cromo - Fonseca, Tiago Oliveira de Belmont (2020)
At present, the use of renewable sources has become an indispensable factor for the use of energy necessary to overcome the energy demand of modern society. In this way, there is the development of an environmental awareness in society creating a need for friendly products, with less environmental impact associated with major technological advances and developments. In this sense, the present work aimed produced chromium-based absorber films, in which the superficial treatment of the AISI 304 stainless steel substrate (cleaning by hexane and mechanical treatment), as well the use of two types of electrolytic baths (B1 and B2) and variations in the electrodeposition time (60, 120 and 300 s). These parameters were used in order to evaluate their influence on the absorption percentage of the films, as in the morphology obtained. The films produced were characterized by Spectroscopy UV-Vis-NIR, FTIR and Optical Profilometry. By the results obtained, it was observed that the deposition time and the type of electrolyte bath great influence on the absorbance percentages of the films produced, where deposition times of 120 s are more viable in terms of economy and absorption, as well as the films requested with type 2 bath (B2) presented the best results with absorption percentages of 97%.